Modulating Both Tumor Cell Death and Innate Immunity Is Essential for Improving Radiation Therapy Effectiveness - Wu, Qiuji; Allouch, Awatef; Martins, Isabelle; Brenner, Catherine; Modjtahedi, Nazanine; Deutsch, Eric; Perfettini, Jean-Luc (Frontiers in Immunology, 2017)
Radiation therapy is one of the cornerstones of cancer treatment. In tumor cells, exposure to ionizing radiation (IR) provokes DNA damages that trigger various forms of cell death such as apoptosis, necrosis, autophagic cell death and mitotic catastrophe. IR can also induce cellular senescence that could serve as an additional anti-tumor barrier in a context-dependent manner. Moreover, accumulating evidence has demonstrated that IR interacts profoundly with tumor-infiltrating immune cells, which cooperatively drive treatment outcomes. Recent preclinical and clinical successes due to the combination of radiation therapy and immune checkpoint blockade have underscored the need for a better understanding of the interplay between radiation therapy and the immune system. In this review we will present an overview of cell death modalities induced by IR, summarize the immunogenic properties of irradiated cancer cells and discuss the biological consequences of IR on innate immune cell functions, with a particular attention on dendritic cells, macrophages and NK cells. Finally, we will discuss their potential applications in cancer treatment.